Penerapan Metode DRASTIC untuk Penilaian Tingkat Kerentanan Air Tanah di Kecamatan Perak Kabupaten Jombang - Handini, Maya; Siswoyo, Hari; Asmaranto, Runi (LPPM Universitas Pekalongan, 2024)
The water source used for daily needs by community in Perak District, Jombang Regency is groundwater. The groundwater in this location has the potential for contamination by domestic waste, so preventive measures are needed to assess the level of groundwater vulnerability. The aim of this research is to assess the level of groundwater vulnerability to pollution and map its distribution. This research was conducted at 25 dug well points in Perak District from July to November 2023. water level (D), rainfall (R), aquifer media (A), soil texture (S), slope (T), unsaturated zone (I), and conductivity. hydraulics (C). Based on the research results, it was found that the DRASTIC index value during the research period ranged from 127 – 167 with medium and high vulnerability. The distribution of groundwater vulnerability levels in the research location is dominated by medium vulnerability with an area between 60 – 72.41%.